2017
DOI: 10.1159/000471931
|View full text |Cite
|
Sign up to set email alerts
|

Perioperative Serum Carcinoembryonic Antigen Levels Predict Recurrence and Survival of Patients with Pathological T2-4 Gastric Cancer Treated with Curative Gastrectomy

Abstract: Background/Aims: Do serum carcinoembryonic antigen (CEA) and carbohydrate antigen (CA) 19-9 levels serve as prognostic indicators in patients with gastric cancer (GC)? This is a question that has long been disputed. The aim of this study was to evaluate the significance of perioperative serum levels of CEA and CA19-9 for predicting the recurrence and long-term survival after patients with pT2-4 GC undergo curative gastrectomy. Methods: This study included 251 patients with radically resected pT2-4 GC without p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 36 publications
0
21
3
Order By: Relevance
“…However, these are invasive procedures with a significant cost for patients. However, noninvasive serum tumor markers such as carcinoembryonic antigen (CEA) and carbohydrate antigen (CA) 19-9 are widely used in clinical practice, but have limited sensitivity and specificity, limiting their utility in decision making and management of patients with gastric cancer [ 6 8 ]. With the development of genomics, proteomics, and metabolomics, an increasing number of biomarkers have been identified and studied [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, these are invasive procedures with a significant cost for patients. However, noninvasive serum tumor markers such as carcinoembryonic antigen (CEA) and carbohydrate antigen (CA) 19-9 are widely used in clinical practice, but have limited sensitivity and specificity, limiting their utility in decision making and management of patients with gastric cancer [ 6 8 ]. With the development of genomics, proteomics, and metabolomics, an increasing number of biomarkers have been identified and studied [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…In previous studies, it has been reported that CEA in serum is an independent prognostic factor, while CEA in tumour tissues is not [15]. Uda et al [16] performed a retrospective study with a median follow-up of 39.6 months in 251 T2-4 GC patients. The 5-year survival rate was significantly lower in the preoperative CEA- positive group than in the CEA-negative group, and this difference was further confirmed in the multivariate analysis.…”
Section: Discussionmentioning
confidence: 99%
“…However, because early GC and LAGC are significantly different in terms of lymph node statue and survival, the predictive value of CEA for determining LNM may be low if the two stages are not separated. In addition, whether preoperative CEA levels can predict the survival of patients with GC is still controversial [11,[14][15][16][17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…The glycoprotein, with a half-life of approximately 7 days, was found to be expressed in gastrointestinal and mucosal tissue during fetal development but only minimally expressed in adult tissue (15,16). Further studies showed that it was also overexpressed in adenocarcinomas of varying origin including gastric, hepatic, lung, pancreatic, ovarian and prostate (17)(18)(19)(20)(21)(22)(23)(24). In colon cancer, the specificity and sensitivity of CEA has been shown to vary with advancing tumor stage, with specificity ranging between 37% and 86% in advanced disease, providing a useful means of monitoring disease (25)(26)(27).…”
Section: Discussionmentioning
confidence: 99%